Sally Madge: acts of reclamation and renewal between site, studio, archive and gallery. (3rd July 2022) - Holt, Ysanne; Hearn, Matthew
ABSTRACT: This article arises from a collaboration between an art historian and a curator in forming an exhibition of work by artist Sally Madge, drawn from a long-accumulated collection of artworks and related materials existing in her basement studio, thereafter housed in a storage container on the outskirts of Newcastle upon Tyne in the North of England. The text is located within evolving discourses on both the curatorial and educational 'turns' in exhibition making and knowledge production, and perceptions of the gallery as a place of shared social and self-determined generative engagement. Emphasising relational interconnectedness, the curation underlines a border-crossing collapsing of categories and hierarchies. The nature of Madge's own practice and the liminal sites she worked in throughout her life reflect a parallel artistic, political and ecological concern for creatively crossing and defying borders and boundaries. What emerges is a dialogue between artist, curator and art historian on questions of transformation and re-representation through the relations between site, studio, archive and gallery.